Mashāʿir in the early Islamic sources: the role of al-azraqi’s “akhbār makkah” - Spahic, Omer (IIUM Press, 2022)
This article discusses the role of al-Azraqi‘s book ―Akhbār Makkah‖ (Reports about Makkah) in the evolution of the Hajj literature and that of the holy cities of Makkah and Madīnah, with special reference to the mashāʿir (ʿArafah, Muzdalifah and Minā). The mashāʿir are dealt with in their capacity as geographical realities, religious notions and signs, and as the venues of a number of Ḥajj rituals. The article concludes that in terms of the Hajj spectacle in general, and the mashāʿirin particular, al-Azraqi‘s book is pioneering. It oscillates between the characters of a history book, that of geography and that of topography. AlAzraqi was the first Muslim scholar to discuss the mashāʿir methodically and in detail. He did so from the perspectives of their religious significance, historical development and existing functions. Al-Azraqi wanted to present a comprehensive picture that could help in mapping out the chronological religious trajectory of Makkah as the holiest place throughout human history, with the mashāʿir playing a significant part. The method adopted in the article is a combination of descriptive and historical interpretation as well as analysis.